1981
DOI: 10.1136/jcp.34.12.1378
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus infection among alcoholic patients with liver disease.

Abstract: 23 February 1981 munehospitalet, Copenhagen, Denmark. In 445 of these 519 patients(86 %) a liver biopsywasperformed.Two hundred and fifty-three of the patients had been diagnosed as having alcoholic liver disease and form the group in our study. Of these 253 patients a histological diagnosis was available in 205 (81 %).The sex ratio between men and women was 2:1. The mean age was 51 yr (range 17-82 yr).The diagnosis was based on anamnestic information of a daily intake of at least 50 g of alcohol for five y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 7 publications
1
8
0
2
Order By: Relevance
“…Em vários estudos foram relatadas maiores prevalências de marcadores sorológicos de infecção pelo VHB em alcoolistas, quando comparados a controles ou à população geral, indicando que alcoolistas apresentam maiores riscos de adquirir esta infecção (1,3,6,13,16,18,20,24,25,27,28,29,30,31) . O comportamento da infecção pelo VHB em alcoolistas foi investigado em alguns trabalhos que apresentaram resultados controversos.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Em vários estudos foram relatadas maiores prevalências de marcadores sorológicos de infecção pelo VHB em alcoolistas, quando comparados a controles ou à população geral, indicando que alcoolistas apresentam maiores riscos de adquirir esta infecção (1,3,6,13,16,18,20,24,25,27,28,29,30,31) . O comportamento da infecção pelo VHB em alcoolistas foi investigado em alguns trabalhos que apresentaram resultados controversos.…”
Section: Introductionunclassified
“…A HB pode apresentar-se como uma forma aguda auto-limitada que evolui para cura, pode ser grave cursando como hepatite fulminante, ou ainda, ter curso crônico, podendo evoluir para cirrose hepática e/ou hepatocarcinoma (21) . Os fatores que influenciam a evolução da doença podem estar relacionados ao hospedeiro (idade de infecção, gênero, estado da imunidade), ao vírus (carga viral, genótipo, mutação) e a causas externas (infecções virais concomitantes, alcoolismo, quimioterapia) (43) .Em vários estudos foram relatadas maiores prevalências de marcadores sorológicos de infecção pelo VHB em alcoolistas, quando comparados a controles ou à população geral, indicando que alcoolistas apresentam maiores riscos de adquirir esta infecção (1,3,6,13,16,18,20,24,25,27,28,29,30,31) . O comportamento da infecção pelo VHB em alcoolistas foi investigado em alguns trabalhos que apresentaram resultados controversos.…”
unclassified
“…Influence of age on development of HBV carrier state has been studied and a consistent relation was found. A study by Chen et al showed a persistent suppression of HBV DNA is important to prevent the development of HCC in known cirrhosis patients [16] . Treatment with the interferon group reduces viral load to undetectable levels with a 50-70% success rate.…”
Section: Introductionmentioning
confidence: 99%
“…A high prevalence of chronic HBV infec tion among alcoholics is a well-recognized phenomenon, but the reasons for it are gen erally unclear [2][3][4][5]. It seems plausible that some immunological factors secondary to the influence of alcohol are involved, since alcoholics present a wide variety of immuno logical disturbances [6], and their response to HBV vaccination is impaired [7], Con trary to expectations, we did not find a higher progression rate to chronic HBV in fection after acute type B hepatitis among alcoholics when compared with non-drink ing controls.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that alcoholics dis play a significantly increased prevalence of antibodies to hepatitis B virus (HBV) anti gens [1][2][3], Furthermore, several studies pointed to a high prevalence of chronic HBV infection among alcohol abusers [2][3][4], The reasons for this phenomenon are generally unknown, although it has been suggested that persistence of HBV infection may be due to compromised immunological re sponse secondary to alcohol consumption [3], We undertook the present study to deter mine the course and outcome of acute type B hepatitis in alcohol abusers.…”
mentioning
confidence: 99%